THE EVALUATION OF THE RATE AND THE TYPE OF MEDICATION ERRORS AMONG NURSES - Pournamdar, Zahra; Zare, Sadegh (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: Since medication instructions are an important part of patients' treatment process, neglecting the correct principles of medication instructions application can result in numerous problems such as unsuccessful treatment or failure and the emergence of lawsuit and complaint issues. The survey and the determination of the medication error types is the first step in preventing them and since the medication errors are common among the nurses according to the various studies and due to their importance the researchers decided to perform a study aiming at the survey of the rate and the type of the medication errors common among the nurses. Methods: This study is a descriptive research performed on 119 nurses from Zahedan training hospitals all of whom have been selected based on a random method in 2016. To gather the necessary information required for the current study, a two-part questionnaire was taken advantage of the first part of which was related to the demographic characteristics, and the second part was connected to the evaluation of the type of medication errors and reporting them. Finally, after the questionnaires were collected, the data were analyzed based on SPSS 19 software and descriptive statistics. Results: The participants average age was 28.86Â±6.45; 101 individuals were women and 87 individuals had passed courses on ethics. Furthermore, 86 nurses had had an experience of medication error at least for 1 time. The highest mean score in the type of the medication error was related to wrong infusion rate, wrong dosage, and administering several drugs without paying attention to the drug interferences.â€ Conclusion: In this study, the results indicated that the rate of the medication errors is a very high among the nurses. Therefore, to reduce the medication errors, there is a need for making serious decisions. Keywords: Medication error, Nurses, Zahedan.